A systematic review of solar driven waste to fuel pyrolysis technology for the Australian state of Victoria. (November 2020) - Hamilton, James; Seyedmahmoudian, Mehdi; Jamei, Elmira; Horan, Ben; Stojcevski, Alex
Abstract: Australia's waste management is heavily dependent on landfill. The Australian Bureau of Statistics predicts that as Australia's population and economy grow, there will be a significant increase in the magnitude of waste output. Concentrated solar driven pyrolysis has been identified as a promising means in creating renewable liquid fuel and improving waste management. This technology is based on the upgrading of waste into a valuable commodity. This is of interest to city councils, communities and stakeholders, as both Australia's annual waste generation and energy demands are growing rapidly. This paper provides a case for the implementation of solar-driven pyrolysis for biofuel production in the Australian state of Victoria as well as a comparative analysis of different Renewable Energy Sources and biomass reactions to justify the combination of Concentrated Solar Power with pyrolysis. This study is the first to assess the solar-driven pyrolysis under a Victorian setting. Victoria was chosen due to the comprehensive and readily available waste data kept by its government. The review concluded that a combination of Fresnel Reflector CSP and pyrolysis are best suited for regional Victorian environment. Fresnel reflector technology was found to complement slow pyrolysis well due to its 250–500◦C operating temperature, while regional Victoria was found to be a good trade-off between feedstock distance and DNI exposure. These requirements were important because feedstock transportation was found to cost AUD 96 per 500km, and it was observed that there could be up to 1200 kWh/m 2 solar exposure difference between Victorian rural and metropolitan locations. This study provides a comprehensive framework of technical requirements pertaining to a Victorian solar-driven pyrolysis system, which will then act as a guidance for future designers.